Trends and mortality effects of vitamin A deficiency in children in 138 low-income and middle-income countries between 1991 and 2013: a pooled analysis of population-based surveys - Gretchen A Stevens, DSc; James E Bennett, PhD; Quentin Hennocq, MSc; Yuan Lu, DSc; Luz Maria De-Regil, DSc; Lisa Rogers, PhD; Goodarz Danaei, MD; Guangquan Li, PhD; Richard A White, PhD; Seth R Flaxman, BA; Sean-Patrick Oehrle, BA; Mariel M Finucane, PhD; et al. (Elsevier, 2015)
Background: Vitamin A deficiency is a risk factor for blindness and for mortality from measles and diarrhoea in children aged 6-59 months. We aimed to estimate trends in the prevalence of vitamin A deficiency between 1991 and 2013 and its mortality burden in low-income and middle-income countries. Methods: We collated 134 population-representative data sources from 83 countries with measured serum retinol concentration data. We used a Bayesian hierarchical model to estimate the prevalence of vitamin A deficiency, defined as a serum retinol concentration lower than 0·70 μmol/L. We estimated the relative risks (RRs) for the effects of vitamin A deficiency on mortality from measles and diarrhoea by pooling effect sizes from randomised trials of vitamin A supplementation. We used information about prevalences of deficiency, RRs, and number of cause-specific child deaths to estimate deaths attributable to vitamin A deficiency. All analyses included a systematic quantification of uncertainty. Findings: In 1991, 39% (95% credible interval 27-52) of children aged 6-59 months in low-income and middle-income countries were vitamin A deficient. In 2013, the prevalence of deficiency was 29% (17-42; posterior probability [PP] of being a true decline=0·81). Vitamin A deficiency significantly declined in east and southeast Asia and Oceania from 42% (19-70) to 6% (1-16; PP>0·99); a decline in Latin America and the Caribbean from 21% (11-33) to 11% (4-23; PP=0·89) also occurred. In 2013, the prevalence of deficiency was highest in sub-Saharan Africa (48%; 25-75) and south Asia (44%; 13-79). 94 500 (54 200-146 800) deaths from diarrhoea and 11 200 (4300-20 500) deaths from measles were attributable to vitamin A deficiency in 2013, which accounted for 1·7% (1·0-2·6) of all deaths in children younger than 5 years in low-income and middle-income countries. More than 95% of these deaths occurred in sub-Saharan Africa and south Asia. Interpretation: Vitamin A deficiency remains prevalent in south Asia and sub-Saharan Africa. Deaths attributable to this deficiency have decreased over time worldwide, and have been almost eliminated in regions other than south Asia and sub-Saharan Africa. This new evidence for both prevalence and absolute burden of vitamin A deficiency should be used to reconsider, and possibly revise, the list of priority countries for high-dose vitamin A supplementation such that a country's priority status takes into account both the prevalence of deficiency and the expected mortality benefits of supplementation. Fundin: Bill & Melinda Gates Foundation, Grand Challenges Canada, UK Medical Research Council.